Abnormal respiratory cilia in non-syndromic Leber congenital amaurosis with CEP290 mutations. Issue 12 (30th August 2010) - Papon, J F; Perrault, I; Coste, A; Louis, B; Gérard, X; Hanein, S; Fares-Taie, L; Gerber, S; Defoort-Dhellemmes, S; Vojtek, A M; Kaplan, J; Rozet, J M; et al.
Abstract : Background: Leber congenital amaurosis (LCA) is the earliest and most severe inherited retinal degeneration. Isolated forms of LCA frequently result from mutation of the CEP290 gene which is expressed in various ciliated tissues. Methods: Seven LCA patients with CEP290 mutations were investigated to study otorhinolaryngologic phenotype and respiratory cilia. Nasal biopsies and brushing were performed to study cilia ultrastructure using transmission electron microscopy and ciliary beating using high-speed videomicroscopy, respectively. CEP290 expression in normal nasal epithelium was studied using real-time RT-PCR. Results: When electron microscopy was feasible (5/7), high levels of respiratory cilia defects were detected. The main defects concerned dynein arms, central complex and/or peripheral microtubules. All patients had a rarefaction of ciliated cells and a variable proportion of short cilia. Frequent but moderate and heterogeneous clinical and ciliary beating abnormalities were found. CEP290 was highly expressed in the neural retina and nasal epithelial cells compared with other tissues. Discussion: These data provide the first clear demonstration of respiratory cilia ultrastructural defects in LCA patients with CEP290 mutations. The frequency of these findings in LCA patients along with the high expression of CEP290 in nasal epithelium suggest that CEP290 has an important role in the proper development of both the respiratory ciliary structures and the connecting cilia of photoreceptors. The presence of respiratory symptoms in patients could represent additional clinical criteria to direct CEP290 genotyping of patients affected with the genetically heterogeneous cone-rod dystrophy subtype of LCA.